PENGARUH TRANSPARANSI KEUANGAN DESA TERHADAP PENGELOLAAN BANTUAN LANGSUNG TUNAI DANA DESA - Nispa Sari; Rifqa Ayu Dasila; Altri Wahida (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study aims to determine the effect of village financial transparency (X) on the management of village fund cash transfers during the pandemic (Y). The data used are primary data by using a questionnaire. The sampling technique used purposive sampling method with a total sample of 95 respondents, namely village officials and several communities receiving village BLT-DD. The data collection technique was a census where all villages in Bajo Barat District were 9 villages. This study uses quantitative research methods and simple linear regression analysis. The results showed that village financial transparency had a positive and significant effect on the management of direct cash assistance from village funds during the covid 19 pandemic. Keywords: village financial transparency, management of direct cash assistance from village funds during the pendemic